Measurement of Radon Levels and Radiological Risk Assessment of Borehole Water in Oil-Producing Area of Ukwuani, Southern Nigeria - Augustine Onyema Nwabuoku (Health Physics, 2026)
A number of communities in Ukwuani Local Government Area of Delta State are known to host several crude oil companies with exploration activities ongoing and may be responsible for the presence of high radon levels in drinking water. Radon ( 222 Rn) has emerged as a major health concern due to its radiotoxic effects and radiation dose to internal organs. Therefore, this work aimed to measure radon levels in borehole water and assess the radiological risk. Thirty water samples were collected from borehole sources in the sampled area into containers. Analysis was done using a RAD7 device for radon measurement. After analysis, radon levels in the samples ranged from 1.373 Bq L −1 to 11.974 Bq L −1 with a mean value of 5.886 Bq L −1 . The average radon value obtained here is below the US Environmental Protection Agency (US EPA) reference level of 11.1 Bq L −1 . The World Health Organization (WHO) recommended limit is also above the mean radon value recorded in this study. This implies that borehole water in Ukwuani LGA is within radon safe limit with no significant threat to human health. These findings provide data to inform policy implementation and support interventions for safe drinking water resources and to serve as reference data for further studies on radon monitoring of other water sources within southern Nigeria.